E-learning for student support, inclusion and equity in diverse post-pandemic teaching contexts (Teacher Education through Flexible Learning in Africa (TETFLE), 2022)
Prior to the onset of the global lockdown, some educators used strategies such as a flipped classroom, blended learning and hybrid learning to integrate the use of technology into the delivery of their modules. This all changed in 2020 when contact sessions were no longer an option to curb the spread of the COVID-19 virus. The result was that educators who partially used e-learning avenues and those who were fully into contact teaching had to make the shift to full online teaching. The pandemic thus brought about an awareness of how much progress we have made and the realisation of how far we still need to go in equitably addressing access and inclusion among students in higher education institutions.The purpose of the study was to explore the extent to which the relationship and partnership between specialists and educators could foster student support for inclusion, access and equity in higher education, thereby informing teacher education. This was a qualitative study with an action research design involving one educator, one e-learning specialist and 110 students across two modules. Affordance theory served as the theoretical framework for the study. Thematic analysis was used to arrive at the salient points and lessons from the partnership.The findings revealed that educators' access to information and technical support allowed them to create supportive learning environments for students. Furthermore, multiple modes of engagement ensured that the probability of diversity being an extenuating factor could be mitigated. Academics must create awareness among students on support interventions available in institutions.
Keywords: E-learning, support, access, equity